Functional analysis of maladaptive behaviors: Rule as a transitive conditioned motivating operation. (February 2016) - Belfiore, Phillip J.; Kitchen, Thomas; Lee, David L.
Highlights: A rule statement may impact occurrence of aberrant behavior in attention situations. A rule may function as a Transitive Conditioned Establishing Operation (CEO-T), asserting that the provision of attention is more valued in the presence of the stated rule. Standard functional analysis conditions may not always be sufficient to produce discernable differences in levels of responding. The plasticity of functional analysis technology allows for stimulus variation within typical analog conditions. Abstract: The purpose of this study was to examine the role of a staff-delivered rule on the occurrence of challenging behavior (stereotypic touching) of an adult with severe intellectual disabilities. Four experimental functional analysis conditions were developed: (a) attention, (b) rule + attention, (c) rule only, and (d) control. Results showed that the percentage of intervals in which stereotypic touching responses (STR) occurred was greater within the experimental condition where a rule statement was embedded with contingent attention. Results are discussed in light of the plasticity of functional analysis technology to allow for stimulus variation within the typical social attention condition, and the suggestion that the rule statement, in this study, may function as a Transitive Conditioned Establishing Operation (CEO-T), asserting that the provision of attention is more valued in the presence of the stated rule.